Testing atmospheric and tidal earthquake triggering at Mt. Hochstaufen, Germany. Issue 10 (17th October 2013) - Hainzl, S.; Ben‐Zion, Y.; Cattania, C.; Wassermann, J.
<x xml:space="preserve">Abstract</x> [1] Seismicity closely related to hydrological impacts has been observed in several locations worldwide, particularly in intraplate areas where tectonic stressing rates are small. The triggering mechanism is usually explained by a poroelastic response of the seismogenic crust to surface water flux, leading to pore pressure changes at depth. To explain the earthquake triggering in response of those small stress changes, however, the crust has to be near a critical state in which other transient processes might be significant. One of the prominent examples is at Mt. Hochstaufen in SE Germany, where seismicity is known to vary seasonally. A previous analysis showed that the seismicity in 2002 was highly correlated with model forecasts based on fluid diffusion and rate‐ and state‐dependent frictional nucleation. Here we revisit this case by accounting additionally for poroelastic effects, as well as for thermoelastic and tidal stresses. We also test whether the model can explain the observations of the subsequent 8 years between 2003 and 2010. Our analysis confirms that rainfall is the dominant driving force in this region. The model not only fits the year 2002 activity very well but also provides with the same parameters a reasonable fit to the subsequent period, with a probability gain of about 4 per event in comparison to a time‐independent Poisson model.